Gratitude training to reduce job stress on people with work-family conflict - Noviati, Nur Pratiwi (Asosiasi Psikologi Islam (API) Himpsi, 2017)
Job stress is the pressure due to the difficult situation encountered in the workplace. Job stress can have a negative impact, decrease in the individuals ability in the completion of tasks. One of the factors that influence job stress is work-family conflict. This study aims to design an intervention that can be reduce job stress on people with work-family conflict. The intervention design created in the form of gratitude training prepared based on the research that has been done before. The study test the correlation between work-family conflict and job stress. Reliability coefficient alpha of job stress scale is 0,765 and work-family conflict scale is 0.930. This preliminary study involving 182 muslim respondents consisting of 118 women and 64 men with age range between 23 years to 60 years. Respondents working at the government service in Yogyakarta spread in 5 places namely the Province of Yogyakarta, Sleman, Bantul, Kulon Progo and Gunung Kidul. The results showed that work-family conflict has positive correlation to job stress (p< 0.00), these indicate that if there are has high work-family conflict, the job stress will be high too. Based on 182 muslim respondents, there are 74 people (46 women and 28 men) who showed the job stress and work-family conflict in the range category of moderate to very high. It means that these respondents experienced a work-family conflict and job stress. The design of interventions in the form of gratitude training is compiled based on the cognitive behavioral approach to gratitude exercise, and the concept of gratitude related to optimization cognitive, affective and psychomotor of participants through the introduction turn back of blessings given from Allah. The steps conducted in the training that is (a) identifying the wrong thoughts (deficiencies, weaknesses or regret over the fate), (b) formulate things that support the mind of gratitude, (c) replace wrong thoughts toward thoughts of gratitude, and (d) applying gratitude in the heart, the thoughts, words and actions. The expectation is the design of gratitude training can be used to reduce work stress on people with work-family conflict.